Preparation and mechanical properties evaluation of polyvinyl alcohol and banana fibres composite. (2020) - Rana, R.S.; Rana, Saraswati; Nigrawal, Archana; kumar, Bipin; kumar, Ashish
Abstract: Now days, the environmental pollution and the prevention of non-biodegradable and non-renewable resources has gained the attraction of the researchers to develop new type of natural materials and products. The fibers obtained from the natural sources supply certain assistance to synthetic fibre materials because of their properties like lower cost, lower density, non-toxicity, comparable strength, and they have no problem while disposing the materials into the environment. Hence in this work, banana fiber have been used as the main reinforcing fibre with polyvinyl alcohol (PVA) resin as the matrix and their samples are prepared to evaluate the mechanical properties of these composites. Hand layup method is used to prepare various types of natural fiber composite such as PVA and Banana fiber. In this method proper dispersion of PVA particles in water is done by conventional magnetic stirring at suitable rpm and assured the proper dispersion of the particle. The tensile strength of prepared PVA and Banana fibre composite is 18.57 Mpa. Percentage elongation of PVA and Banana fiber based fiber composite is 9.1%. Flexural strength investigate 10.2 Mpa for 30 g of filler concentration. It can be widely used in food packaging due to its good biodegrading efficiency and adequate strength for handling.